2002
DOI: 10.2337/diabetes.51.10.3033
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitively Controls the Glucagon Response to Mild Hypoglycemia in the Dog

Abstract: In the present study, we examined how the arterial insulin level alters the ␣-cell response to a fall in plasma glucose in the conscious overnight fasted dog. Each study consisted of an equilibration (؊140 to ؊40 min), a control (؊40 to 0 min), and a test period (0 to 180 min), during which BAY R 3401 (10 mg/kg), a glycogen phosphorylase inhibitor, was administered orally to decrease glucose output in each of four groups (n ‫؍‬ 5). In group 1, saline was infused. In group 2, insulin was infused peripherally (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The current data suggest that the decrease in glucose provoked by systemic insulin administration may be not only perceived as a signal of metabolic deprivation but also seen as a signal of concomitant food availability, thereby resulting in a muted or maladaptive glucagon response. It is noteworthy that a similar enhancement of glucagon secretion has been reported with drug-induced insulin-independent decrements in blood glucose in the dog, which was attributed to suppression of intraislet insulin, but that is equally consistent with the loss of the central inhibitory actions of insulin (47). One might speculate that the loss of glucagon response to hypoglycemia in type 1 diabetic patients lacking endogenous insulin might result in part from the simultaneous increase in insulin levels both in the VMH and locally in the islet caused by exogenous insulin administration.…”
Section: Discussionsupporting
confidence: 63%
“…The current data suggest that the decrease in glucose provoked by systemic insulin administration may be not only perceived as a signal of metabolic deprivation but also seen as a signal of concomitant food availability, thereby resulting in a muted or maladaptive glucagon response. It is noteworthy that a similar enhancement of glucagon secretion has been reported with drug-induced insulin-independent decrements in blood glucose in the dog, which was attributed to suppression of intraislet insulin, but that is equally consistent with the loss of the central inhibitory actions of insulin (47). One might speculate that the loss of glucagon response to hypoglycemia in type 1 diabetic patients lacking endogenous insulin might result in part from the simultaneous increase in insulin levels both in the VMH and locally in the islet caused by exogenous insulin administration.…”
Section: Discussionsupporting
confidence: 63%
“…Although the frequency and total number of hormone samples in our experiments were insufficient to derive a precise glycemic threshold, correlation of hormone levels against blood glucose indicated that epinephrine, corticosterone, and glucagon increased in mice at glucose levels that were close to 80 mg/dl. This level is notably higher than the 60 -70 mg/dl threshold reported for responses of these counterregulatory hormones to insulininduced hypoglycemia in humans and dogs (25,39) and suggests that the same blood glucose level may not represent the same stimulus severity in all species. We did not observe hypoglycemia-induced increases in plasma norepinephrine, but elevated norepinephrine is not a consistent feature of counterregulation in other species (14,29,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 54%
“…Redundant mechanisms appear to control glucagon secretion in the normal state. The alpha cell is able to respond sensitively to the glycemic level in hypoglycemia, but this ability is ablated in the presence of even very mild hyperinsulinemia (29). The decrement in intraislet insulin that occurs during hypoglycemia is reported to be related to the magnitude of the glucagon response (3,23,33,36).…”
Section: Discussionmentioning
confidence: 99%